Industry 5.0 : the future of the industrial economy - Elngovan, Uthayan (CRC Press, Taylor & Francis Group, 2022)
Technology has created innovative new prospects for manufacturing industries with Industry 4.0 and has helped further the growth of the manufacturing sector. This book focuses on the next stage, which is Industry 5.0, and the steps in taking automation to that next level by increasing processes and operational efficiency, as well as reducing workforce size. Industry 5.0: The Future of the Industrial Economy discusses the integration of product, process, machine, software, and industrial robots in realizing Industry 5.0. It covers the dual integration of human intelligence with machine intelligence and reviews the results of making use of Industrial Internet of Things (IIoT) and Artificial Intelligence (AI). The creation of a new category of robots named Collaborative Robots (Cobots) specifically designed to speed up the manufacturing process and profitability is explored. This book also explores how to reduce waste in product design through the manufacturing process and offers more personalized and customized products for customers. Manufacturing, design, industrial, and mechanical engineers, as well as practicing professionals, will find this book of interest. Management executives, CIOs, CEOs, IT professionals, and academics will also find something of value in this book that takes Industry 4.0 to Industry 5.0 and beyond
Keywords: ekonomika průmyslu; průmyslová automatizace; průmyslová revoluce -- 21. století; industrial economics; industrial automation; industrial revolution -- 21st centuries; průmysl 5.0; monografie; monographs